Ethnobotanical Survey of Plants used for Cancer Treatment in Akinyele Local Government of Ibadan, Nigeria and Preliminary Cytotoxic Activity of Selected Plants (Nigerian Journal of Pharmaceutical Research, 2021)
Background: In Nigerian ethnomedicine, a few anticancer constituents of medicinal plant of natural products have been reported in the literature. Although several traditional medical practitioners (TMPs) have claimed to have managed this disease with plants that have been in existence from ancient times.Objective: This study aimed at the documentation and validation of plants that are commonly used in the treatment of cancer in Akinyele Local Government of Oyo State, Nigeria.Materials and methods: Focus-Group discussion and administration of semi-structured questionnaires were used to discover the practice of traditional medicine using plants. The methanol extracts of the commonly cited plants were then screened for cytotoxicity using the Brine shrimp lethality (BSL) and in vitro [3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyl tetrazolium bromide (MTT) assay. Two cancer (Rhabdomyosarcoma; RD and cervical; Hep-2C) and normal (Vero) cell lines were used for the screening of the extracts.Results: A total number of 45 Traditional Medical Practitioners and herb sellers were recruited for this study, 26 different plants were recorded with their local names and parts used for therapeutic preparation. Two plant extracts; Aframomum melegueta and Strophanthus hispidus were found to be active against the cancer cell lines and selective to normal cell line used.Conclusion: Some of the plants had cytotoxic properties on the cancer cell lines which supports the claims of the Traditional Medicinal Practitioners. However, the non-selectivity of some plants to normal cells could be a great threat to the cancer patients being treated.
Keywords: Ethnobotanical survey; Cancer; Conservation of knowledge